Substance misuse prescribing challenges during the pandemic. Issue 11 (16th November 2021) - McAuley, D. Michael
Abstract : The COVID‐19 pandemic has necessitated a paradigm shift in the way substance misuse services are delivered, with a move from face‐to‐face to remote consultations. This article discusses the challenges substance misuse healthcare providers have faced adapting to these changes and how technological innovations have helped ensure treatments are prescribed or supplied as safely as possible.